The Political Essays by Mario Vargas Llosa: from Communist Populism to Classic Liberalism - Sánchez-Costa, Enrique (Populismo y propaganda: entre el presente y el pasado, 2020)
Mario Vargas Llosa, from the beginning, accompanied his narrative work with an incisive, controversial and audacious essay work. This study will follow, through his political essay, its evolution from the youthful communism (Sartre and the Cuban Revolution, whose communism can be labelled as populist) to the classical liberalism of its maturity (the free market of Adam Smith and Von Hayek, the philosophy of Ortega y Gasset and Popper, or the political ideas of Isaiah Berlin). Finally, it will underline the central role played by literature both in its first communist enthusiasm as in its subsequent disenchantment.